Synodality as the Kernel of Pope Francis’ Ecclesiology: Implications for Missionary Dynamism for the Church in Africa - Anyanwu, Ugochukwu Stophynus (Asian Horizons, 2020)
Synodality has gained renewed currency during the Pontificate of Pope Francis. In keeping with the programme of aggiornamento of the Second Vatican Council, Pope Francis has continued an insightful exploration of the Trinitarian and communio ecclesiology that are at the heart of a synodal Church. Synodality is the specific modus vivendi et operandi of the Church, the People of God, which reveals and gives substance to her being as communion when all her members journey together, gather in assembly and take an active part in her evangelizing mission. In this essay, I will attempt to show that Synodality is at the heart of Pope Francis’ Ecclesiology. This essay will also be an effort in contextual theology, especially in proposing for the Church in Africa some ecclesiological models that can help her re-launch her missionary dynamism in the third millennium.